2016
DOI: 10.1038/ncomms13599
|View full text |Cite
|
Sign up to set email alerts
|

A redox mechanism underlying nucleolar stress sensing by nucleophosmin

Abstract: The nucleolus has been recently described as a stress sensor. The nucleoplasmic translocation of nucleolar protein nucleophosmin (NPM1) is a hallmark of nucleolar stress; however, the causes of this translocation and its connection to p53 activation are unclear. Using single live-cell imaging and the redox biosensors, we demonstrate that nucleolar oxidation is a general response to various cellular stresses. During nucleolar oxidation, NPM1 undergoes S-glutathionylation on cysteine 275, which triggers the diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 86 publications
(142 reference statements)
4
112
0
Order By: Relevance
“…Cellular stress triggers its dissociation from nucleolar nucleic acids and translocation from the nucleus to the nucleolus, which activates p53 to DNA binding and p53dependent apoptosis. Using live-cell imaging and redox biosensors, Yang et al (91) have demonstrated that NPM1 undergoes glutathionylation on Cys 275 , which triggers its dissociation from nucleolar nucleic acids. In contrast, its mutant protein C275S (cys/ser substitution) could not be glutathionylated and remained bound to DNA under nucleolar stress.…”
Section: P53mentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular stress triggers its dissociation from nucleolar nucleic acids and translocation from the nucleus to the nucleolus, which activates p53 to DNA binding and p53dependent apoptosis. Using live-cell imaging and redox biosensors, Yang et al (91) have demonstrated that NPM1 undergoes glutathionylation on Cys 275 , which triggers its dissociation from nucleolar nucleic acids. In contrast, its mutant protein C275S (cys/ser substitution) could not be glutathionylated and remained bound to DNA under nucleolar stress.…”
Section: P53mentioning
confidence: 99%
“…A recent clinical application of actinomycin D caused substantial remission in patients with acute myeloid leukaemia. This GSH involvement and manipulation with its active binding site on NPM in nucleolar stress sensing may help to develop therapeutic strategies (91).…”
Section: P53mentioning
confidence: 99%
“…Previous data have shown both that NPM1 is a nucleolar/ribosomal stress-induced nucleolar protein and that the interaction between NPM1 and NNV capsid protein may represent a mechanism that is crucial to NNV infection (Mai et al, 2016;Yang et al, 2016). Thus, we hypothesized that RGNNV may induce nucleolar/ribosomal stress via NPM1.…”
Section: Rgnnv Induces Nucleolar/ribosomal Stress In Gs Cellsmentioning
confidence: 96%
“…The p53-dependent response relies on the disruption of the interaction between p53 and Mdm2/Hdm2, which results in p53 stabilization and activation. For example, NPM1 undergoes S-glutathionylation upon nucleolar oxidative stress, translocates to the nucleoplasm, and disrupts the p53-Hdm2 interaction [105]. Interestingly, over the last years, several studies have shown that most of the p53-dependent but also p53-independent stress responses are dependent on the activity of free ribosomal proteins (RPs) that have been shown to perform multiple extra-ribosomal functions, including regulation of apoptosis, cell cycle arrest, cell proliferation, and DNA damage repair [106,107].…”
Section: Neddylation In the Nucleolar Stress Responsementioning
confidence: 99%